Contracting Balance in Islamic Banking Mudharabah Agreements in Indonesia: Islamic Economic Perspective - syarifuddin, syarifuddin; Djaenab; Nuringsih (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2024)
The purpose of this study is to determine the position of mudharabah contracts in fiqh and the practice of mudharabah contracts in Islamic banking in Indonesia in general. The research method used by the author in this research is literature review, data collection through several journals, and several other references, then data analysis uses review analysis using data reduction, systematic and objective. The results of this study reveal that the mudharabah contract is a collaboration between the owner of the funds or investors (shaihb al-mal / rabb al-mal / investors) and the manager of capital (mudharib) to do business on the basis of a profit sharing ratio. Although mudharabah contracts have no basis in the Koran or implicit sunnah, they were used to carry out trade by the early generations of Muslims. Contracts are developed by the Fuqaha under conditions on his behalf based on general sharia principles of fairness. Islamic banking practices in carrying out mudharabah contracts as financing in the case of mudharabah contracts are one of the banking products, namely in the form of time savings, for example hajj savings, sacrifices, and special savings (special investments)